Simultaneous Bilateral Spontaneous Pneumothorax in an HIV Positive Tuberculosis Patient - Arie Gradiyanto Nugroho; Edijono Edijono; Sri Sarwosih Indah Marthaty (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2023)
Background: Even though tuberculosis has been linked to pneumothorax for a long time and has caused significant morbidity and mortality in some patients, it has been the topic of few publications and analyses, thus very little study has been done to evaluate and review on this matter.Case: In this article, we reported a 39-year-old male, presented to the ER with breathlessness for the last 3 days accompanied by increased sputum productivity. The patient had an active pulmonary tuberculosis taht was under treatment, as well as HIV. Physical examination showed low chest expansion, weakened breathing sounds on both lungs, and the use of accessory breathing muscles. The chest X-ray showed bilateral pneumothorax. The patient underwent emergency chest decompression with a 16-gauge needle on both sides, followed by the insertion of an IPC and chest tube. The patient's breathlessness got significantly better, and after 35 days, the IPC was removed.Discussion: Pneumothorax is a frequent complication in Tuberculosis with HIV, with a prevalence of 6.8% compared to 0.95-1.4% in Tuberculosis without HIV. The progression of breathlessness in bilateral pneumothorax on HIV positive Tuberculosis patient is slower, up to 3 days since onset, compared to pneumothorax occured in other etiologies. Secondary pneumothorax usually occurs after extensive destruction of the lungs, leaving a little functionality and lower cardiopulmonary reserve, thus requiring prompt evaluation and more aggresive lifesaving treatment.Conclusion: Based on this case, bilateral pneumothorax found in HIV-associated TB patients comes with an insidious onset but warrants immediate evaluation and aggressive treatment or surgery if necessary.